Aberrant Cortical Integration in First-Episode Psychosis During Natural Audiovisual Processing - Mäntylä, Teemu; Nummenmaa, Lauri; Rikandi, Eva; Lindgren, Maija; Kieseppä, Tuula; Hari, Riitta; Suvisaari, Jaana; Raij, Tuukka T. (Biological psychiatry (1969), 2018)
Functional magnetic resonance imaging studies of psychotic disorders have reported both hypoactivity and hyperactivity in numerous brain regions. In line with the dysconnection hypothesis, these regions include cortical integrative hub regions. However, most earlier studies focused on a single cognitive function at a time, assessed by delivering artificial stimuli to patients with chronic psychosis. Thus, it remains unresolved whether these findings are present already in early psychosis and whether they translate to real-life–like conditions that require multisensory processing and integration. Scenes from the movie Alice in Wonderland (2010) were shown to 51 patients with first-episode psychosis (16 women) and 32 community-based control subjects (17 women) during 3T functional magnetic resonance imaging. We compared intersubject correlation, a measure of similarity of brain signal time courses in each voxel, between the groups. We also quantified the hubness as the number of connections each region has. Intersubject correlation was significantly lower in patients with first-episode psychosis than in control subjects in the medial and lateral prefrontal, cingulate, precuneal, and parietotemporal regions, including the default mode network. Regional magnitude of between-group difference in intersubject correlation was associated with the hubness. Our findings provide novel evidence for the dysconnection hypothesis by showing that during complex real-life–like stimulation, the most prominent functional alterations in psychotic disorders relate to integrative brain functions. Presence of such abnormalities in first-episode psychosis rules out long-term effects of illness or medication. These methods can be used in further studies to map widespread hub alterations in a single functional magnetic resonance imaging session and link them to potential downstream and upstream pathways.